Relations between Spectrum Curves of Discrete Sturm-Liouville Problem with Nonlocal Boundary Conditions and Graph Theory. II - Vitkauskas, Jonas; Štikonas, Artūras (Lietuvos matematikos rinkinys, 2021)
In this paper, relations between discrete Sturm--Liouville problem with nonlocal integral boundary condition characteristics (poles, critical points, spectrum curves) and graphs characteristics (vertices, edges and faces) were found. The previous article was devoted to the Sturm--Liouville problem in the case two-points nonlocal boundary conditions.
Keywords: Sturm-Liouville problem; spectrum curves; integral boundary condition; graphs